2016
DOI: 10.1242/jeb.129338
|View full text |Cite
|
Sign up to set email alerts
|

Center of mass velocity based predictions in balance recovery following pelvis perturbations during human walking

Abstract: In many simple walking models, foot placement dictates the center of pressure location and ground reaction force components, whereas humans can modulate these aspects after foot contact. Because of the differences, it is unclear to what extent predictions made by models are valid for human walking. Yet, both model simulations and human experimental data have previously indicated that the center of mass (COM) velocity plays an important role in regulating stable walking. Here, perturbed human walking was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
217
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(237 citation statements)
references
References 32 publications
16
217
4
Order By: Relevance
“…Once an unintended perturbation occurs, foot placement is even more critical in restoring stability. Vlutters et al (2016) found that recovery from medial-lateral perturbations on treadmill walking involved medial-lateral foot placement adjustments proportional to the medial-lateral COM velocity. Hof (2008) reported that changes in foot placement were associated with stability after perturbations in walking.…”
Section: Discussionmentioning
confidence: 93%
“…Once an unintended perturbation occurs, foot placement is even more critical in restoring stability. Vlutters et al (2016) found that recovery from medial-lateral perturbations on treadmill walking involved medial-lateral foot placement adjustments proportional to the medial-lateral COM velocity. Hof (2008) reported that changes in foot placement were associated with stability after perturbations in walking.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Madehkhaksar et al [10] found that in order to increase dynamic stability immediately after perturbation, young adults walk with shorter, wider strides and a higher cadence, with a stronger response to medio-lateral than to anterior-posterior perturbations. Vlutters et al [14] found similar results when applying perturbations to the hip during walking stating that "at heel strike after the perturbation, recovery from medio-lateral perturbations involved medio-lateral foot placement adjustments proportional to the medio-lateral center of mass velocity. In contrast, for anteroposterior perturbations, no significant anteroposterior foot placement adjustment occurred".…”
Section: Introductionmentioning
confidence: 84%
“…The most extensively studied mechanism to stabilize gait is foot placement (Bauby and Kuo, 2000, 51 Townsend, 1985, Wang and Srinivasan, 2014, Vlutters et al, 2016. Foot placement is considered the main 52 mechanism for stabilizing gait in the AP movement direction (but also in mediolateral (ML) direction) 53 (MacKinnon and Winter, 1993, Patla, 2003.…”
Section: List Of Symbols and Abbreviationsmentioning
confidence: 99%
“…A second mechanism is to apply active muscle moments 54 around the ankle of the stance foot ('ankle strategy') (Horak and Nashner, 1986). Experimental data showed 55 that humans adjust sagittal plane muscle moments around the ankle of the stance foot following AP 56 mechanical perturbations of gait (Vlutters et al, 2016) (but also frontal plane muscle moments following 57 ML perturbations (Hof and Duysens, 2018)). These ankle moments are reflected in a shift of the center of 58 pressure of the ground reaction force (CoP).…”
Section: List Of Symbols and Abbreviationsmentioning
confidence: 99%